Total laparoscopic hysterectomy: a new alternative endoscopic surgery - Celis, Alfredo (2015)
Objective: To evaluate the role of total laparoscopic hysterectomy in the treatment of uterine pathology. Design: Descriptive and retrospective study. Material and Methods: Seventy two patients with indication of abdominal hysterectomy underwent total laparoscopic hysterectomy (TLH) employing the "RUMY manipulator and Koh Colpotomiser System" at the Gynecology Service of Edgardo Rebagliati Martins Hospital during 1998-2000. Laparoscopy was the method for total hysterectomy and electrosurgical energy was the only coagulation method. The surgical technique, postoperative evolution and complications were evaluated. Results: Seventy six interventions were scheduled, four suffered conversion to laparotomy due to severe adhesions. Mean age of patients was 46,1 years old, mean weight 63,7 kg, mean hospitalization 3,3 days. Mean surgical time was 144 minutes and mean uterine length 12,1 cm (range 10-18). Urologic injuries represented the mayor complications of TLH, present in four cases: one ureteral injury and three vesical injuries (5,5%), and 79% of all complications were present in the first 37 cases (51%). Conclusions: Total laparoscopic hysterectomy represents a safe and technically feasible procedure and future studies will establish its exact place and precise indications.